Fats Conversion in the Technological Processing and their Detection of Falsification - Kononchuk, Victoria; Arsenieva, Larisa (My University, 2014)
During the study, the quality of oils and fats should be also determined the fatty acid composition and the ratio of cis- and trans- isomers of fatty acids.
Keywords: butter adulteration; фальсифікація вершкового масла; жирні кислоти; fatty acids; кафедра експертизи харчових продуктів